Indonesian Legal Remedies Againts Tiongkok and Vietnam Dumping in Indonesia - Rahmadi Indra Tektona; Nuzulia Kumala Sari; Amru Hanifa Mukti (Metafora: Education, Social Sciences and Humanities Journal, 2021)
Indonesia has a problem increasing the number of iron and steel imports from year to year, but Tiongkok and Vietnam are highlighted differently by government because they have experienced a significant increase, so they are suspected of dumping. And than, what the legal remedies should be taken against the alleged dumping carried out by Tiongkok and Vietnam by competent institutions and related parties and what the legal consequnces are. This research will be analyzed with normative legal research principles, legal doctrines, and international agreements with the law approach and conceptual approach.The Antidumping Code is the basis of Indonesias efforts towards Tiongkok and Vietnam given that the three countries are remembers of the World Trade Organization with General Agreement on Tariff and Trade. The Indonesian Anti-Dumping Committee is an institution that is given the authority to conduct dumping investigations, both offensively or defensively wich is inisiated based on initiatives or requests from the majority of the Domestic Industry of the similar goods. If the investigation process carried out by KADI is proven to be found dumping it will be subject sanctions in the form of the imposition of Anti-Dumping Import Duty according to the amount of dumping margin and if it is not found or deministic margin then the investigation process is terminated. And it is unfortunate because dumping specifically has not been regualated in a law in Indonesia.